Clinical Effects of Laser Acupuncture plus Chinese Cupping on the Pain and Plasma Cortisol Levels in Patients with Chronic Nonspecific Lower Back Pain: A Randomized Controlled Trial. (7th August 2017) - Lin, Mu-Lien; Wu, Jih-Huah; Lin, Chi-Wan; Su, Chuan-Tsung; Wu, Hung-Chien; Shih, Yong-Sheng; Chiu, I-Ting; Chen, Chao-Yi; Chang, Wen-Dien
Abstract : Objectives . Chronic nonspecific lower back pain (LBP) is a common disease. Insufficient data is currently available to conclusively confirm the analgesic effects of laser acupuncture on LBP. This study evaluated the effectiveness of laser acupuncture plus Chinese cupping in LBP treatment. Methods . Patients with chronic nonspecific LBP were enrolled for a randomized controlled trial and assigned to the laser acupuncture group (laser acupuncture plus Chinese cupping) and control group (sham laser plus Chinese cupping). Laser acupuncture (808 nm; 40 mW; 20 Hz; 15 J/cm 2 ) and Chinese cupping were applied on the Weizhong (BL40) and Ashi acupoints for 5 consecutive days. Plasma cortisol levels were assessed before and after the 5-day treatment session. The visual analog scale (VAS) scores were recorded at baseline and throughout the 5-day treatment session. Results . After the treatment session, the plasma cortisol levels and VAS scores decreased significantly in both groups. In the laser acupuncture group, the VAS scores decreased significantly on days 4 and 5, and an enhanced reduction in VAS scores was observed. Conclusion . Laser acupuncture plus Chinese cupping at the Weizhong (BL40) and Ashi acupoints effectively reduced pain and inflammation in chronic nonspecific LBP. This therapy could be a suitable option for LBP treatment in clinical settings.